TANTANGAN DAN PERUBAHAN DALAM PENDIDIKAN AGAMA ISLAM DI ERA MILLENNIAL - Qonita Masyithah; Wedra Aprison (CV. ADIBA AISHA AMIRA, 2024)
Islamic education faces significant challenges in the millennial era, characterized by technological advancements and globalization. With their unique characteristics, the millennial generation requires a paradigm shift in Islamic education. This article discusses the necessary changes in crucial elements of Islamic education, such as vision, mission, goals, curriculum, and teaching methods, while preserving the values of the Quran and Hadith. Placing Islam as the primary perspective in education is crucial to understanding and integrating the spiritual values of Islam into the daily lives of the millennial generation. To remain relevant and contribute to building a civil society in Indonesia during the reform era, the reconstruction of the Islamic education paradigm must be done carefully, blending tradition with contemporary developments.